Validity of ESQ booklets about structure and function of animal tissue as biology learning supplement - Fadhilah Ikhtiarni; Ardi; Rahmawati Darussyamsu (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2021)
The development of an ESQ booklet on the structure and function of animal tissues to empower students' emotional-spiritual attitudes in schools has not been maximized. This research aims to develop an ESQ booklet about the structure and function of animal tissue and to determine the validity of the booklet. This research type is research and development (R&D). This learning media was developed using three stages of the 4D model namely define, design, and develop. The research instruments used are observation sheets, interview transcripts, and validity test sheets. The research data collected through questionnaires of validity test sheets to content expert, media expert, ESQ expert (Islamic religion teacher), and biology teacher. The assessment of each validator was analyzed and processed using the validity formula and adjusted to the validity category. Based on the analysis of the validity test questionnaire, it was found that the validity percentage of the content eligibility was 92.05%, the linguistic aspect was 92.16%, the presentation aspect was 93.33%, and the graphics aspect was 95.83%, all of the criteria is very valid. It was concluded that the ESQ booklet about the structure and function of animal tissue as a biology learning supplement was categorized as very valid with an average score is 93.34%. Thus, the conclusion of the research is that the ESQ booklet about the structure and function of animal tissue as a biology learning supplement is declared very valid from the aspects of content, language, and media.